Jan Lechoń in Front of the Mirror of the Tribunal of Conscience - Urbańska, Monika; Agnieszka Gralak (Lustro, 2020)
Jan Lechoń hid his face under the mask of Konrad, creating himself as the heir of the great romantics, the fourth bard. In reflections on the mirror’s topics, along with Erynie poem, his Diary is the basic source that allows to understand the various stages of Lechoń creativity, the periods of his creative collapse, and the internal path in which the writer made regular vivisection. Bills of conscience, spiritual confrontations with the glass of the mirror, in Diary was called by him as the „court of justice”. However, he was not honest in his records, he made many silences. Portraits of total destruction were not an option in the case of Lechoń, he wanted to keep the face that was needed — to the end. Throughout his life and consistently, in the final moment, Lechoń remained a prisoner of form and mask. We will discuss this topic in the article.